Optimizing the Structural Properties of CdO Nanoparticle Thin Films as a Function of Temperature (Journal of the College of Basic Education, 2022)
A thin film on glass substrates of cadmium oxide (CdO) nanoparticles was prepared by thermal vacuum technique. The films were annealed at (300, 350 and 425) °C for 2 h. The impact of thermal treatment change on the structure and micro-structural properties was observed. XRD and AFM analysis confirms that the CdO films are a polycrystalline cubic structure and the preferred growth orientation along (111) plane, which it has a texture coefficient at 1.261, 1.310, 1.355 and 1.124 values for before and after annealing the films. The grain size increases from 73.79 nm to 86.17 nm as annealing temperature increases. The result of scanning electron microscopy (SEM) was proved of presence nanostructures with homogeneous a characteristic nano-grain size and different shapes for all the films